Traumatic Brain Injury Activation of the Adult Subventricular Zone Neurogenic Niche - Chang, Eun Hyuk; Adorjan, Istvan; Mundim, Mayara V.; Sun, Bin; Dizon, Maria L. V.; Szele, Francis G. (Frontiers in Neuroscience, 2016)
Traumatic brain injury (TBI) is common in both civilian and military life placing a large burden on survivors and society. However, with recognition of neural stem cells in adult mammals, including humans, came the possibility of harnessing these cells for repair of damaged brain tissue, previously thought to be a lost cause. In this review we focus on the adult subventricular zone (SVZ), an important neurogenic niche within the mature brain in which neural stem cells continue to reside. We review how the SVZ is perturbed following various animal traumatic brain injury models with regards to cell proliferation, emigration, survival and differentiation, and we review specific molecules involved in these processes. Together, this information suggests next steps in attempting to translate knowledge from animal models of TBI into human therapies for TBI.